(untitled) (Eurasian Scientific Herald, 2022)
In the context of liberalization and transformation of the economy, the creation of a multi-sectoral economy in agriculture is an important issue. Therefore, the government of the republic is also focusing on reforming the agricultural sector, creating a new structure in its form and content. The basis for the transformation of the agricultural sector will be the use of agricultural achievements of Western countries and the introduction of world best practices in agriculture. This will lead to a more consistent, scientific study of the financing system of the sector and a structural review of the current state of financing the agricultural sector.